Cutaneous manifestations in inflammatory bowel disease: a single institutional study of non‐neoplastic biopsies over 13 years. (26th August 2016) - Ko, Jennifer S.; Uberti, Georgina; Napekoski, Karl; Patil, Deepa T.; Billings, Steven D.
Abstract : Background: Skin is commonly affected by extraintestinal manifestations of inflammatory bowel disease (IBD), but a controlled, systematic histopathologic analysis of cutaneous lesions is lacking. Methods: A total of 4147 classified IBD [Crohn disease (CD) or ulcerative colitis (UC); 2000–2013] resections were cross referenced with skin biopsies. Associated non‐neoplastic skin biopsies were categorized by basic reaction pattern and neutrophilic vs. granulomatous. Results: Of 4147 patients, 133 had non‐neoplastic skin biopsies (106/2772, 3.7% CD; 27/1375, 2% UC). Overall, miscellaneous > nodular and diffuse dermal > spongiotic dermatitides were most common (31.6, 21.8 and 15%, respectively). Spongiotic dermatitis, vasculitis, panniculitis and infections showed CD bias. Psoriasiform, perivascular, nodular/diffuse dermal and bullous categories, as well as neutrophilic processes, showed UC bias. Leukocytoclastic vasculitis, panniculitis and pyoderma gangrenosum were exclusive to CD and psoriasis vulgaris to UC. One CD patient had inverse psoriasis. Conclusions: Our findings show the majority of dermatopathologic manifestations of IBD to have overlapping histology or pathophysiology to intestinal disease; with a wider spectrum of histologic patterns than typically discussed. Diseases 'classically' associated with IBD are relatively rare biopsy specimens. Cutaneous manifestations of IBD are more common in CD than UC and should be considered when reviewing an unexplained skin lesion in an IBD patient.